2016
DOI: 10.3389/fpsyg.2016.01140
|View full text |Cite
|
Sign up to set email alerts
|

Finger Forces in Clarinet Playing

Abstract: Clarinettists close and open multiple tone holes to alter the pitch of the tones. Their fingering technique must be fast, precise, and coordinated with the tongue articulation. In this empirical study, finger force profiles and tongue techniques of clarinet students (N = 17) and professional clarinettists (N = 6) were investigated under controlled performance conditions. First, in an expressive-performance task, eight selected excerpts from the first Weber Concerto were performed. These excerpts were chosen to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Hofmann and Goebl8 explored the finger force profiles and tongue techniques of clarinet students and professional clarinetists under controlled performance conditions. Their study found that the finger force varied between different body types and sex (Hofmann, 2016). The results yielded an average flexion force of 1.17 N. The largest force of 1.21 N was recorded during high expression level performance conditions, which is consistent with other researcher's findings who used dynamometers (Silva, et al, 2005).…”
Section: Methodssupporting
confidence: 78%
“…Hofmann and Goebl8 explored the finger force profiles and tongue techniques of clarinet students and professional clarinetists under controlled performance conditions. Their study found that the finger force varied between different body types and sex (Hofmann, 2016). The results yielded an average flexion force of 1.17 N. The largest force of 1.21 N was recorded during high expression level performance conditions, which is consistent with other researcher's findings who used dynamometers (Silva, et al, 2005).…”
Section: Methodssupporting
confidence: 78%
“…In order to measure the reed-tip displacement and to trace the tongue-reed interaction, the reed vibration is measured with a strain gauge (length of 2 mm) attached to the surface of a synthetic reed (strength 2.5, German cut, by Légère), as used in Hofmann and Goebl (2016). The external sound is recorded under dry acoustic conditions, with a microphone (d:vote 4099U, by DPA) mounted on the instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Governing Equations: The strip of aluminum that will be inserted in the polymer finger support can be treated as a cantilever thin plate, because there is no force or movement at the base of the support. As mentioned before (Hofmann and Goebl, 2016), the amount of maximum force exerted by fingers was found to be 1.21N, which is considered here. Since the aluminum strip will be treated as a thin plate, the common formulas for bending stress and deformation can be applied.…”
Section: Methodsmentioning
confidence: 82%
“…According to their methodological study conducted on finger force when playing some instruments, a healthy finger force varied with different test subjects of different body types and sex. Gathered from the research studies (Hofmann and Goebl, 2016), an average finger flexion force can be considered as 120gf which converts to 0.2644lbf or 1.177N. However, they also expressed that the largest finger force during the high expression level performance conditions was increased to 1.21N which is considered for this present work.…”
Section: Methodsmentioning
confidence: 93%